POLITIK PEMBANGUNAN HUKUM KEKUASAAN KEHAKIMAN PASCA REFORMASI 1998 BERDASARKAN UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - Yuli Heriyanti; Ahmad Zikri; Tobing, Firmansyah L (Jurnal Pahlawan, 2022)
The main basis for the existence of judicial power is regulated in Article 24 Paragraph (2) of the 1945 Constitution, namely "judicial power is exercised by a Supreme Court and judicial bodies under it in the general court environment, religious court environment, military court environment, state administrative court environment, and by a Constitutional Court. This choice is actually similar to what is done by 78 other countries in the world. Where, in addition to the Supreme Court (Supreme Court), independent courts are formed which are generally named the Constitutional Court (Constitutional Court). Thus, judicial power will be exercised by two courts simultaneously. The formulation of the problem in this study is which institutions are the perpetrators of judicial power in Indonesia according to Law Number 48 of 2009, and what are the politics of legal development from Law Number 48 of 2009 concerning the new Judicial Power in the reform era. This research is a normative juridical research, this emphasizes more on the conception of the rules relating to changes in judicial power in accordance with the goals and politics of legal development for the future. Keywords: politics, legal development, judicial power.